Late Triassic melting of a thickened crust in southeastern China: Evidence for flat-slab subduction of the Paleo-Pacific plate - Zhu, Kong-Yang; Li, Zheng-Xiang; Xu, X.; Wilde, Simon (Pergamon-Elsevier Science Ltd, 2013)
The Dashuang complex in Zhejiang Province of southeast China is composed of two distinct lithologies: syenite in the west and quartz monzonite in the east. They record similar zircon U–Pb ages of 224 ± 3 Ma (syenite), and 226 ± 2 Ma and 227 ± 1 Ma (quartz monzonite), respectively, but are notably different in petrography, magnetic susceptibility, whole-rock chemistry, zircon Hf isotope and zircon trace element characteristics. The west Dashuang syenitic pluton (the west body) has high modal alkali feldspar, high zircon saturation temperatures, high whole-rock and zircon MREE/HREE ratios, low Fe–Mg–Ti contents, and is depleted in Ba, Sr and Eu. It also has low magnetic susceptibilities, belongs to the ilmenite-series, and is a peraluminous and ferroan granitoid. The east Dashuang quartz monzonitic pluton (the east body) has abundant K-feldspar megacrysts, with hornblende, titanite and biotite being the major ferromagnesian minerals. In contrast to the west body, the east body has lower zircon saturation temperatures, lower whole-rock and zircon MREE/HREE ratios, higher Fe–Mg–Ti contents, and shows no depletion in Ba, Sr or Eu.The east body has higher magnetite contents, high magnetic susceptibilities and belongs to the magnetite-series. It is a metaluminous and magnesian granitoid of arc-affinity. Zircon Hf isotopic data reveal that both bodies were derived from partial melting of Paleoproterozoic igneous protoliths in the lower crust, but the east body possibly incorporated subducted terrigenous sediments. Both bodies have higher melting temperatures and pressures than adjacent Cretaceous granitoids, reflecting their origin in a thickened, hotter lower crust. The most feasible model to explain their differences is variations in water content during crustal melting, resulting in different melting and crystallization behaviors. Such melting in a Triassic thickened crust with variable water involvement, followed by Cretaceous magmatism in an extensional setting, is consistent with the flat-slab subduction model proposed for South China. The model involves crustal thickening and partial melting, with mantle and lower crustal metasomatism during flat-slab propagation in the Triassic–Early Jurassic, and crustal thinning and extension from the mid-Jurassic to the Cretaceous.